The Enhancement of African American Existence in Suzanne Lori Park's The America Play. : تعزيز الوجود الأفريقي الأمريكي في مسرحية سوزان لوري باركس "مسرحية امريكا (مجلة ديالى للبحوث الانسانية, 2023)
.     Social elevation, as the main concept of this  study that is discussed by Suzanne Lori Parks in her play The America play (1993), is an attempt by the playwright to encourage her people to reconsider  their history and their true place through the medium of theatre. This study explores the theme of social elevation by adopting the social identity theory of Henry Tajfel (1970s) promoting a sense of belonging to the African American experience. Parks also discusses the theme of digging and investigating the importance of the hole as a metaphor used by her to rewrite history through her distinct metaphorical style, which enables her to clearly highlight her ideas. According to Parks, African-American heritage has not been discussed fairly. As a result, she should trace her ancestors' existence through American history in order to improve their lives in society. This study also examines the social elevation of African American identity through the use of Abraham Lincoln as a symbol of American liberty. It portrays the character of the simple black gravedigger, or "Foundling Father," who abandoned his wife and son to impersonate Abraham Lincoln in a park known as the Great Hole of History. The America Play draws a strong parallel between the lesser-known Foundling Father and Abraham Lincoln, the president. It depicts Lincoln's role as the real American President in the lives of African Americans.